Every Learner Matters : Unpacking the Learning Crisis for Children With Disabilities - World Bank Group (World Bank, Washington, DC, 2019)
Aligned with the message of the World Bank’s 2018 World Development Report: Learning to Realize Education’s Promise, ‘Every Learner Matters’ argues that for children with disabilities, the focus needs to shift from school access to prioritizing learning. This paper examines education systems and the importance of measuring learning achievement for children with disabilities to respond appropriately to the needs of students. Assessments are needed to promote learning and equip teachers with appropriate skills to address classroom diversity, and not exclusively as a tool to measure what is taught. Similarly, it is vital to ensure participation for children with disabilities in high-stakes regional and international assessments, which guide education policies and can direct national budgetary allocations in education.